Techniques and Tools for Reliability Assessment of Power Systems - Natalija Petrova, Nevenka Kiteva Rogleva, Vangel Fustik (ETAI - Society for Electronics, Telecommunications, Automatics and Informatics of the Republic of Macedonia, 2018)
The power system is a complex system consisting of more subsystems that are complex. Each of these subsystems has an impact on the reliability and security of the system as a whole. The functioning of the elements of this system, such as busbars, lines, switches, can affect the quality of delivered electricity as well as the reliability of the system. This paper initially defines the types of defects that can occur in the transmission and distribution grid. Then, the application of Mark’s processes is considered for determining the frequency of failures and repairing of some of the electrical equipment. In the second part a model of the power system developed in the program package Neplan is given. An analysis of the system in normal operation and in the event of a fault has been made, and also, the estimates of defects of individual elements of the power system. In addition, criteria is established on which one can make a list for replacement, rehabilitation and reconstruction of the elements of the power system in order to reduce its operating costs for operating and maintaining the reliability and security of the power system as a whole.
Keywords: electrical equipment; reliability, defect